2014
DOI: 10.1021/jp411130n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Starch Polymorphic Structures Using Vibrational Sum Frequency Generation Spectroscopy

Abstract: The polymorphic structures of starch were characterized with vibrational sum frequency generation (SFG) spectroscopy. The noncentrosymmetry requirement of SFG spectroscopy allows for the detection of the ordered domains without spectral interferences from the amorphous phase and also the distinction of the symmetric elements among crystalline polymorphs. The V-type amylose was SFG-inactive due to the antiparallel packing of single helices in crystal unit cells, whereas the A- and B-type starches showed strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 57 publications
(128 reference statements)
9
59
0
1
Order By: Relevance
“…The 2,904 cm -1 peak does not match the positions of typical primary cell walls (2,920, 2,964 and 3,320 cm -1 ) or secondary cell walls (2,850, 2,944 and 3,320 cm -1 ) Kafle et al 2014b). However the 2,904 cm -1 peak does coincide with the SFG feature of starch (Kong et al 2014). Starch is the main form of glucose storage in plant cells; SFG detected starch in the primary cells of Arabidopsis aerial tissues ).…”
Section: Discussionmentioning
confidence: 91%
“…The 2,904 cm -1 peak does not match the positions of typical primary cell walls (2,920, 2,964 and 3,320 cm -1 ) or secondary cell walls (2,850, 2,944 and 3,320 cm -1 ) Kafle et al 2014b). However the 2,904 cm -1 peak does coincide with the SFG feature of starch (Kong et al 2014). Starch is the main form of glucose storage in plant cells; SFG detected starch in the primary cells of Arabidopsis aerial tissues ).…”
Section: Discussionmentioning
confidence: 91%
“…Wide-angle X-ray scattering (WAXS) of purified and dried glucans resulted in a diffraction pattern typical of many starches, where glucan chains form double helices that align with an inter-helical spacing of ~1.6 nm, indicative of a B-type allomorph (Kong et al, 2014; Figure 6D). Small-angle X-ray scattering (SAXS) indicated that the helices were stacked in a weakly ordered lamellar structure with a periodicity of 13.6 nm (Figure 6E), slightly longer than typically reported for plant starches (PĂ©rez and Bertoft, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the band at 2900-2950 cm −1 , also seen in all samples, was assigned to CH stretching of the axial methane group in the ring and CH 2 stretching of the exocyclic CH 2 OH side group of the amylose chain. It is interesting to note that the band at 2900-2950 cm −1 for amylose microparticles prepared in the presence of fatty acids was relatively less intense than that prepared in the absence of fatty acids, suggesting that the order of the amylose double helix crystal array was decreased by the presence of the fatty acids (Kong, Lee, Kim, & Ziegler, 2014;Schuster, Ehmoser, Gapes, & Lendl, 2000). However, the representative fatty acid band expected at 1640-1660 cm −1 for an excitation wavelength of 785 nm (Nimz, Gessler, UsĂłn, Sheldrick, & Saenger, 2004) was not observed for any of the amylose microparticles, including those synthesized with fatty acids (Fig.…”
Section: Production Of Amylose Microparticles In the Presence Of Fattmentioning
confidence: 99%